Imaginaries and the Commons: Insights From Irrigation Modernization in Valencia, Spain - Jaime Hoogesteger; Vivian Konijnenberg; Lieke Brackel; Sjoerd Kemink; Michiel Kusters; Bas Meester; Anusha Sanjeev Mehta; Tjalling ‘t Hart; Mark van der Poel; Pippi van Ommen; Rutgerd Boelens; Carles Sanchis-Ibor (International Journal of the Commons, 2023)
In this article we introduce the notion of imaginaries as a conceptual entry to study and better understand how and why commons re-create and transform. We do so by first exploring imaginaries as assemblages, and second by analytically dividing imaginaries in dominant and alternative imaginaries. While the former refer to how people imagine and live their social existence around built expectations and their underlying notions, the latter refers to imaginaries that critique instituted society and through it create ‘germs’ that can lead to transformation. Through this lens we analyze contestations that have emerged around the introduction of drip irrigation in two irrigation communities in the Valencia Region of Spain. These two case studies (Carcaixent and Potries) show how, among the commons, alternative imaginaries are challenging the dominant imaginaries of drip irrigation. We show how these alternative imaginaries result from a different way of assembling irrigation and the social, cultural, material, and economic relations around it. These insights, we argue, open up avenues that allow us to better understand the imaginary creations that reproduce a specific existing order, as well as the germ(s) that can lead to transformations and change.